2020
DOI: 10.1111/pcmr.12870
|View full text |Cite
|
Sign up to set email alerts
|

Do innate killing mechanisms activated by inflammasomes have a role in treating melanoma?

Abstract: Melanoma, as for many other cancers, undergoes a selection process during progression that limits many innate and adaptive tumor control mechanisms. Immunotherapy with immune checkpoint blockade overcomes one of the escape mechanisms but if the tumor is not eliminated other escape mechanisms evolve that require new approaches for tumor control. Some of the innate mechanisms that have evolved against infections with microorganisms and viruses are proving to be active against cancer cells but require better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“… 5 , 23 , 101 , 102 It is worth mentioning that recent studies have shown that other caspases, including caspase-3/4/5/6/8/9/11, also cause pyroptosis in other different cells, 16 , 17 , 29 , 39 , 94 , 103 105 and play major roles in innate immunity and tumorigenesis. 106 111 Caspase-3 was previously thought to be the executor of apoptosis, but it was suggested that caspase-3 can also induce pyroptosis by cleaving GSDME. 16 , 17 , 71 More surprisingly, the apoptosis-related protein caspase-8 can also directly cleave GSDMD to induce pyroptosis.…”
Section: The Characteristics Of Pyroptosismentioning
confidence: 99%
“… 5 , 23 , 101 , 102 It is worth mentioning that recent studies have shown that other caspases, including caspase-3/4/5/6/8/9/11, also cause pyroptosis in other different cells, 16 , 17 , 29 , 39 , 94 , 103 105 and play major roles in innate immunity and tumorigenesis. 106 111 Caspase-3 was previously thought to be the executor of apoptosis, but it was suggested that caspase-3 can also induce pyroptosis by cleaving GSDME. 16 , 17 , 71 More surprisingly, the apoptosis-related protein caspase-8 can also directly cleave GSDMD to induce pyroptosis.…”
Section: The Characteristics Of Pyroptosismentioning
confidence: 99%
“…UV-induced chronic inflammation orchestrates the interactions of melanoma and immune cells at the tumor milieu, in favor of immune escape and therapeutic resistance [ 3 , 4 ]. This has urged the need for a better biological understanding of the melanoma microenvironment, while also forming the motivation for revolutionizing melanoma treatment in the last decade [ 5 , 6 ]. The gold standard treatment for this condition is surgery, followed by systemic chemo and immunotherapy in more advanced stages [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless our previous analysis of melanoma patient data in the TCGA showed that high levels of AIM2, NLRP3, NLRC4 and NLRP1 were associated with a good prognosis (Emran et al, 2020). The prognostic benefit of NLRP3 and NLRP1 was only seen in patients with high TIL levels suggesting the benefit was dependent on immune responses rather than intrinsic properties of the cells (Emran et al, 2020). Other preclinical studies have pointed to the importance of activation of inflammasomes in immune cells as mediators of responses against tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Renewed interest in chemotherapy has also been stimulated by discovery of innate death mechanisms that can be activated by chemotherapy (Emran et al, 2020). These include ferroptosis that results from iron dependent lipoxygenase enzyme peroxidation of polyunsaturated fatty acids in cell membranes, necroptosis that is induced by death receptor ligands in cells with low or absent caspase-8 levels and pyroptosis that results from activation of inflammasomes and release of gasdermins (GSDMs).…”
Section: Introductionmentioning
confidence: 99%